2014
DOI: 10.1155/2014/247595
|View full text |Cite
|
Sign up to set email alerts
|

The Spectroscopy Study of the Binding of an Active Ingredient of Dioscorea Species with Bovine Serum Albumin with or without Co2+ or Zn2+

Abstract: Diosgenin (DIO) is the active ingredient of Dioscorea species. The interaction of DIO with bovine serum albumin (BSA) was investigated through spectroscopic methods under simulated physiological conditions. The fluorescence quenching data revealed that the binding of DIO to BSA without or with Co2+ or Zn2+ was a static quenching process. The presence of Co2+ or Zn2+ both increased the static quenching constants K SV and the binding affinity for the BSA-DIO system. In the sight of the competitive experiment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Xiao et al observed a decrease in the IL-8 expression in Helicobacter pylori-induced infection through the action of microRNA-155 on the IKKε segment specific for NF-kB and TLR signaling [163]. Wu et al reported on the implications of microRNA-23b on the modulation mechanisms for the expression of NF-κB, IL-6, TNF-α, and VCAM-1 [164]. Li et al, in a similar study, observed a reduction in TNF-α activity, and in the IL-1β expression modulated by microRNA-33 [165].…”
Section: Micrornas Expression In Sepsis-induced By Cannabinoid Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao et al observed a decrease in the IL-8 expression in Helicobacter pylori-induced infection through the action of microRNA-155 on the IKKε segment specific for NF-kB and TLR signaling [163]. Wu et al reported on the implications of microRNA-23b on the modulation mechanisms for the expression of NF-κB, IL-6, TNF-α, and VCAM-1 [164]. Li et al, in a similar study, observed a reduction in TNF-α activity, and in the IL-1β expression modulated by microRNA-33 [165].…”
Section: Micrornas Expression In Sepsis-induced By Cannabinoid Signalmentioning
confidence: 99%
“…Stripada et al have also shown mitochondrial expression for let-7b, let-7g, microRNA-107, microRNA-221, microRNA-181a, and microRNA-320a [163]. Bian et al have carried out a study on microRNA expression in mouse liver and have identified a series of mitochondrial microRNA such as microRNA-202-5p, microRNA-223, microRNA-122, microRNA-134, microRNA-720, microRNA-790, microRNA-155, microRNA-494, and microRNA-680 [164]. It has been proven that mitochondrial activity modulation by microRNA takes place after they bind to the mitochondrial RNA subtypes on the 5' 2-8nt sequences.…”
Section: Micrornas Expression In Sepsis-induced By Cannabinoid Signalmentioning
confidence: 99%